Satisfaction and Professional Mobility: A Franco-Argentine Study About PhD, in the Light of a Sui Generis Paradigm - Aparicio, Miriam Teresita (2016)
The research dealt with PhD graduates who had obtained their degrees from 2005 onwards and PhD students from different courses of study belonging to Cuyo University (UNCuyo, Argentina) and CNAM (France). The purpose was to analyze the relation between professional mobility and professional satisfaction, variables hard to reach a competitive and uncertain work world and within education institutions which do not always train adequately in the competences required by the market. Associated to them, we analyzed the professionalization factor and the identity strategies involved in confronting theproblems at work. The methodology used was quantitative (statistical analysis) but mainly qualitative (interviews and hierarchical evocations). This technique shows which aspects enter into the focus of the representations of the doctors regarding the relation of education/work and of the conditioning factors of achievement, and which aspects are “peripheral”. The analysis was carried out from Dr. Aparicio’s approach—The Theory of Three Dimensional Spiral of Sense—i.e., in the light of three‐level interplay: micro, meso, and macro levels. Also, we took as reference the “Expectancy‐Valence Theory” and the Theory of Education as “Consumption or Investment”. The results show non‐linear but spiral (in feedback) relations between the variables of the model (psycho‐social, organizational, and structural factors) according to disciplinary fields and national contexts.